In Silico Bahan Aktif Epigallocatechin Gallate dari Sargassum cristaefolium untuk Menghambat Pembentukan Interleukin 1B pada Sindroma Mata Kering - Muhammad Nabil Faiq; Irma A. Pasaribu; Tamam Jauhar; Verna Biutifasari (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Dry eye syndrome is a multifactorial condition that disrupts the tear film and ocular surface, causing discomfort, visual disturbances, and damage to the ocular surface. Sargassum cristaefolium, a brown alga found in Indonesia, contains the active compound Epigallocatechin gallate (EGCG), which has anti-inflammatory potential. EGCG can inactivate interleukin-1B signaling, thereby triggering the activation of MMPs that play a role in epithelial barrier degradation and maintaining lubrication of the corneal surface. EGCG also exhibits functions comparable to Cyclosporin A, a drug used for dry eye syndrome. This study aims to determine the performance of EGCG in suppressing interleukin-1B to inhibit the production and activation of MMPs through an in-silico approach. The method involves several stages, namely molecular docking, ADME prediction, and toxicity prediction of the active compound EGCG. EGCG is predicted to have potential equivalent to Cyclosporin A in inhibiting interleukin-1B. EGCG shows advantages such as good distribution in blood plasma, no effect on CYP3A4 enzymes, and no influence on OCT2 substrates. In addition, EGCG has a slower excretion rate, is non-mutagenic, does not cause skin sensitization, and is non-hepatotoxic. Thus, EGCG found in Sargassum cristaefolium may serve as an anti-inflammatory agent and inhibit interleukin-1B protein in dry eye syndrome through in silico mechanisms.